: Online Mindfulness-Based Program for Metastatic Gastrointestinal Cancer Patients and Caregivers - Hannah M. Dragomanovich; Anand Dhruva; Eve Ekman; Kelly L. Schoenbeck; Ai Kubo; Erin L. Van Blarigan; Hala T. Borno; Mikaela Esquivel; Bryant Chee; Matthew Campanella; Errol J. Philip; John P. Rettger; et al. (SAGE Publishing, 2021)
Purpose A metastatic cancer diagnosis is associated with high levels of distress in patients and caregivers, which may be alleviated by mindfulness interventions. Research on scalable, tailored, online mindfulness training programs is needed. We sought to test the feasibility and acceptability of a remotely delivered 8-week mindfulness-based intervention, Being Present 2.0 (BP2.0). Methods We performed a single-arm feasibility study of BP2.0 among patients with any metastatic gastrointestinal cancer receiving chemotherapy, with or without an informal caregiver. Participants were instructed to practice mindfulness using pre-recorded guided meditations 5 times per week using a study-specific website and to attend a weekly live, interactive virtual meeting facilitated by a trained instructor. The web-based platform enabled direct measurement of adherence. Results The study enrolled 46 of 74 (62%) patients contacted, together with 23 caregivers (69 participants total), from May to October 2018. Median patient age was 52 (range 20-70 years), 39% were male, 67% non-Hispanic white, 65% had colorectal cancer, and 78% lived outside of San Francisco. The top reasons cited for participation were to reduce stress/anxiety and learn how to meditate. Mean baseline National Comprehensive Cancer Network Distress Thermometer (NCCN DT) scores were 4.7 (patients) and 5.8 (caregivers). The study discontinuation rate was 20% (eight patients and six caregivers). Among the remaining 55 participants, 43 (78%) listened to at least one audio recording and/or attended at least one virtual meeting, although adherence data was incomplete. The retention rate was 71%, with 39 participants completing at least one follow-up assessment. In post-intervention qualitative interviews, 88% of respondents reported a positive experience. Compared to baseline, participants reported significantly reduced post-intervention NCCN DT scores (mean 3.1; P = .012). Conclusion The BP2.0 online mindfulness-based program is feasible and acceptable for patients with metastatic gastrointestinal cancer and caregivers. These results will guide plans for a follow-up efficacy study. ClinicalTrials.gov Identifier: NCT03528863.